IMPLEMENTATION OF LITERACY PROGRAM THROUGH TAHFIDZ LEARNING WITH TALAQQI METHOD IN MUHAMMADIYAH ORPHANAGE - Eli Triana; Enceng Mulyana (IKIP Siliwangi Bandung, 2020)
This research aims to describe the literacy program's implementation through takhfidz learning with the talaqqi method in Muhammadiyah orphanage, starting from planning, implementation, results, and factors affecting the literacy program. The research method used is descriptive quality. The data collection techniques that the authors use in this study are through observations and interviews conducted with teachers and students., documentation studies, and literature studies. The analysis of the data used is to begin providing raw data, such as field records and research documents, storing and researching the results of research in the form of field records and documents, formulating views or interpretations, drawing conclusions, and reporting the entire research process. The results showed that: 1) Planning literacy programs through takhfidz learning with talaqqi methods in Muhammadiyah orphanages include: a) Identification of learning needs and learners, b) Formulating learning objectives, c) Strategizing learning activities, d) Determining the implementing team of learning, e) Preparing learning facilities and materials, f) Determination of learning methods and techniques, g) Determination of place and time of learning, and h) Determination of learning costs. 2) The implementation of learning consists of three activities, namely the initial activity (opening), this activity, and the last activity (closing). 3) The result of learning is that there is an improvement in the reading skills of the Qur'an, now the child can know and mention various hijaiyyah letters, read and know short letters in juz 30, and can memorize them well. 5) Supporting factors include teacher factors that use demonstration and guidance methods and the use of exciting media to appeal to the child. The factors that hinder the learning process are the environmental factors of the house that are less supportive.